Degradation of Emerging Plastic Pollutants from Aquatic Environments Using TiO2 and Their Composites in Visible Light Photocatalysis - Alexandra Gabriela Stancu; Maria Râpă; Cristina Liana Popa; Simona Ionela Donțu; Ecaterina Matei; Cristina Ileana Covaliu-Mirelă (Molecules)
This review synthesized the current knowledge on the effect of TiO2 photocatalysts on the degradation of microplastics (MPs) and nanoplastics (NPs) under visible light, highlighting the state-of-the-art techniques, main challenges, and proposed solutions for enhancing the performance of the photocatalysis technique. The synthesis of TiO2-based photocatalysts and hybrid nanostructured TiO2 materials, including those coupled with other semiconductor materials, is explored. Studies on TiO2-based photocatalysts for the degradation of MPs and NPs under visible light remain limited. The degradation behavior is influenced by the composition of the TiO2 composites and the nature of different types of MPs/NPs. Polystyrene (PS) MPs demonstrated complete degradation under visible light photocatalysis in the presence of α-Fe2O3 nanoflowers integrated into a TiO2 film with a hierarchical structure. However, photocatalysis generally fails to achieve the full degradation of small plastic pollutants at the laboratory scale, and its overall effectiveness in breaking down MPs and NPs remains comparatively limited.